Image restoration of one-dimensional inorganic compounds in single-walled carbon nanotubes - Friedrichs, S; Meyer, R; Sloan, J; Kirkland, A; Hutchison, J; Green, M (2001)
The growth behaviour and crystallography of metal halides incorporated within single walled carbon nanotubes (SWNT) has been studied by an enhanced image restoration technique which restores the object wave from a focal series of HRTEM images. This allows the structural characterisation of the encapsulated crystals with a precision not normally achievable from single HRTEM images. The restored phase provides information about the atomic thickness in projection of individual atom columns, and reveals precise structural data concerning lattice distortions within the crystal fragments relative to the bulk structures. In most cases, substantial overall lattice contractions of the crystal along the tube axis were observed. The smallest observed crystals were as thin as two atomic layers in projection along the image plane normal.